2017
DOI: 10.3389/fpls.2017.01550
|View full text |Cite
|
Sign up to set email alerts
|

Oomycete Communities Associated with Reed Die-Back Syndrome

Abstract: Phragmites australis (Cav.) Trin. ex Steud. die-back is a widely-studied phenomenon that was first discovered in northern Europe and that, until recently, was almost unknown in the Mediterranean basin. It has been described as a complex syndrome affecting reed populations leading to their retreat and decline, with significant impacts on valuable ecosystem services. Among the factors that cause the decline, soil-living microorganisms can be crucial. The aims of this study were to analyze the diversity of oomyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 56 publications
3
18
0
Order By: Relevance
“…The two nested PCR approaches, DC6/ITS7 x Oom18S / ITS7 (PERO_ITS) and Oom18S/ITS7 × 5.8S1R/18ph2F (PHYTO_ITS), proved reliable for qualitative characterisation of mock Phytophthora communities without other Oomycete species. However, the second PCR strategy was much more effective for environmental samples, usually containing a much higher abundance of other Peronosporaceans such as Pythium (Cerri et al 2017). Moreover, the number of amplified Phytophthora species corresponded to the order of magnitude of Phytophthora diversity in temperate forests, which is of about 2 to 8 species (Jung et al 2010;Hansen and Delatour 1999).…”
Section: Fig 2 Proportions Of Reads Permentioning
confidence: 99%
“…The two nested PCR approaches, DC6/ITS7 x Oom18S / ITS7 (PERO_ITS) and Oom18S/ITS7 × 5.8S1R/18ph2F (PHYTO_ITS), proved reliable for qualitative characterisation of mock Phytophthora communities without other Oomycete species. However, the second PCR strategy was much more effective for environmental samples, usually containing a much higher abundance of other Peronosporaceans such as Pythium (Cerri et al 2017). Moreover, the number of amplified Phytophthora species corresponded to the order of magnitude of Phytophthora diversity in temperate forests, which is of about 2 to 8 species (Jung et al 2010;Hansen and Delatour 1999).…”
Section: Fig 2 Proportions Of Reads Permentioning
confidence: 99%
“…The microorganisms associated with Phragmites populations have been implicated in its performance in a variety of settings worldwide. For instance, in native European populations, bacterial and oomycete communities in the rhizosphere correlated with stages of decline in populations affected by reed die‐back syndrome (Bacci et al., 2018; Cerri et al., 2017). Likewise, several authors have suggested the key to understanding the invasive nature of non‐native Phragmites in North America may lie in microbial associations (Clay et al., 2016; Kowalski et al., 2015; Shearin et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in sequencing technologies and computational analysis have revealed how plants host a myriad of microorganisms, collectively referred to as the microbiota, whose interactions at given plant sites define the plant microbiome ( Schlaeppi and Bulgarelli, 2015 ). The characterization of the microbiota of land plants has been gaining momentum both in basic and translational science ( Hacquard et al, 2015 ), yet elucidating the functional significance of the wetland plants microbiota is a research field in its infancy ( Bowen et al, 2017 ; Cerri et al, 2017 ). For instance, roots of wetland plants offer a unique site of colonization with access to oxygen and organic resources for microorganisms otherwise thriving in water.…”
Section: Introductionmentioning
confidence: 99%